Studi Literatur Peran Blockchain Technology Dalam Sistem Informasi Akuntansi Untuk Transparansi Laporan Kinerja Dan Efisiensi Audit - Diah Hari Suryaningrum; Nania Nuzulita (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study addresses the persistent challenges of limited transparency and inefficiency in accounting information systems, particularly in the context of financial reporting and auditing. It aims to examine the role of blockchain in enhancing transparency and improving audit processes within accounting systems. The research adopts a systematic literature review approach by analyzing 43 selected academic articles and relevant industry reports published between 2019 and 2026. The analysis focuses on identifying key characteristics, mechanisms, and implications of blockchain adoption in accounting practices. The findings indicate that blockchain has strong potential to improve data transparency, traceability, and reliability through features such as distributed ledgers, immutability, and smart contracts. These characteristics support real-time financial reporting and enable more continuous and efficient audit processes. The study also identifies several implementation challenges, including regulatory uncertainty, high adoption costs, and limited professional expertise. Furthermore, this research proposes a conceptual framework integrating blockchain into accounting information systems to support better governance and decision-making. The study contributes to the growing discourse on digital transformation in accounting, particularly in emerging economies.